2019
DOI: 10.1016/j.jcot.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intra- and Extramedullary Implants in Treatment of Unstable Intertrochanteric Fractures

Abstract: Introduction: Comparison was made of the clinical and radiological results of the surgical treatments of proximal femoral nail (PFN), dynamic hip screw (DHS) or proximal femoral locking compression plate (PF-LCP) in patients with AO 31A2.2/2.3 unstable intertrochanteric femoral fracture(ITF). Methods: Evaluation was made of a total of 91 patients in respect of age, gender, time from fracture to surgery, operating time, amount of blood replacement, total hospitalisation, follow-up period, time to full weight-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…Deceased patients who were excluded from the studies' final analyses were included in this study's analysis. This was not possible for Duymus et al, [57] as the number of deceased patients excluded was unavailable.…”
Section: Data Categoriesmentioning
confidence: 99%
“…Deceased patients who were excluded from the studies' final analyses were included in this study's analysis. This was not possible for Duymus et al, [57] as the number of deceased patients excluded was unavailable.…”
Section: Data Categoriesmentioning
confidence: 99%
“…Duymus et al compared the result of intra- and extramedullary implants in treatment of intertrochanteric fractures and found that proximal femoral nail had better clinical results. The full weight-bearing time was significantly reduced to 1.25 ± 0.40 months 21 .…”
Section: Discussionmentioning
confidence: 90%
“…All of these factors may have influenced the identification of the osseous union and affected the assessment of complications. Third, we also could not clearly document when the patient started weight bearing even though some studies regard the time to weight bearing as an important parameter for evaluating the stability of implant fixation [25,26]. A comparison of surgical incision length between the two implants was also not performed in our study.…”
Section: Study Limitationsmentioning
confidence: 90%